1995
DOI: 10.1101/lm.2.3-4.185
|View full text |Cite
|
Sign up to set email alerts
|

Temporal specificity of long-term depression in parallel fiber--Purkinje synapses in rat cerebellar slice.

Abstract: The phenomenon of cerebellar long-term depression (LTD), a decrease of synaptic strength between the parallel fibers (PFs) and Purkinje cells after conjunctive activation of PFs and the climbing fibers (CFs), is implicated as a cellular mechanism for motor learning. We have characterized a field-potential recording technique in cerebellar slice and have used the technique to examine the temporal conditions for cerebellar LTD induction in an attempt to examine the relevance of LTD to associative conditioning, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
82
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(89 citation statements)
references
References 45 publications
6
82
1
Order By: Relevance
“…The precise interval of time between granule cell and climbing fiber activation that is required for induction of LTD remains under investigation. Reported effective intervals have ranged from presynaptic first by 250 msec (Chen and Thompson, 1995) to climbing fiber first by 125 msec (Ekerot and Kano, 1989). Because we find that the results do not differ significantly for this range of intervals, our choice of a 0 msec interval (i.e., simultaneous activity in gr3Pk j synapse and climbing fiber input) represents a consensus interval that allows induction of LTD under a variety of experimental conditions (Ekerot and Kano, 1989;Karachot et al, 1994;Chen and Thompson, 1995).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The precise interval of time between granule cell and climbing fiber activation that is required for induction of LTD remains under investigation. Reported effective intervals have ranged from presynaptic first by 250 msec (Chen and Thompson, 1995) to climbing fiber first by 125 msec (Ekerot and Kano, 1989). Because we find that the results do not differ significantly for this range of intervals, our choice of a 0 msec interval (i.e., simultaneous activity in gr3Pk j synapse and climbing fiber input) represents a consensus interval that allows induction of LTD under a variety of experimental conditions (Ekerot and Kano, 1989;Karachot et al, 1994;Chen and Thompson, 1995).…”
Section: Methodsmentioning
confidence: 99%
“…Reported effective intervals have ranged from presynaptic first by 250 msec (Chen and Thompson, 1995) to climbing fiber first by 125 msec (Ekerot and Kano, 1989). Because we find that the results do not differ significantly for this range of intervals, our choice of a 0 msec interval (i.e., simultaneous activity in gr3Pk j synapse and climbing fiber input) represents a consensus interval that allows induction of LTD under a variety of experimental conditions (Ekerot and Kano, 1989;Karachot et al, 1994;Chen and Thompson, 1995). The reversibility of plasticity at gr3Pk j synapses is at present an assumption of the simulation because the evidence to date suggests that LTP-LTD at this synapse are not mutually reversible because the expression of the former seems to be presynaptic (Salin et al, 1996), whereas that of the later is clearly postsynaptic (Linden, 1994).…”
Section: Methodsmentioning
confidence: 99%
“…Paired stimulation of parallel and climbing fibers induces LTD (Chen & Thompson, 1995;Schreurs, Oh, & Alkon, 1996;Freeman, Shi, & Schreurs, 1998), but parallel fiber stimulation without climbing fiber stimulation can induce LTP (Sakurai, 1987;Salin, Malenka, & Nicoll, 1996). It is possible that the parallel fiber-alone stimulation that presumably occurs during the non-reinforced compound stimulus in conditioned inhibition training induces LTP in Purkinje cells.…”
Section: Introductionmentioning
confidence: 99%
“…Several models argue that long-term depression (LTD) of parallel fiber inputs to Purkinje cells is a learning mechanism involved in excitatory conditioning (Albus, 1971;Gluck, Reifsnider, & Thompson, 1990;Kim & Thompson, 1997;Mauk, 1997;Mauk et al, 1998;Mauk & Donegan, 1997;Thompson & Krupa, 1994;Thompson, 2000;Yeo & Hesslow, 1998). LTD has been demonstrated in vitro using parallel fiber stimulation followed by climbing fiber stimulation, a protocol which resembles delay conditioning (Chen & Thompson, 1995;Freeman, Shi, & Schreurs, 1998;Schreurs, Oh, & Alkon, 1996). Moreover, several studies have shown changes in Purkinje cell simple spike activity that are consistent with the LTD hypothesis (Foy, Krupa, Tracy, & Thompson, 1992;Gilbert & Thach, 1977;Hesslow & Ivarsson, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism of decremental plasticity might contribute to Pavlovian learning through disinhibition of neurons of the NI that, as we have seen, seem to be the central role of plasticity. In a study by Chen and Thompson (1995), using an in vitro preparation, maximum LTD was observed after stimulation of parallel fibers was preceded by 250 ms stimulation of climbing fibers. These temporal parameters are similar to those effective for behavioral learning or for the neurophysiological conditioning previously described.…”
Section: Two Forms Of Synaptic Plasticity Mediate Eyelid Conditioningmentioning
confidence: 99%